A preparation method of low conductivity coolant and low conductivity coolant
By introducing porous magnesium silicate-based adsorbent into the ethylene glycol/water coolant, the anions and cations in the coolant are adsorbed, and the problem of rising conductivity of the coolant is solved, achieving the effect of low conductivity and long service life.
Patent Information
- Application Number
- CN202211505226.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-29
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-11-29
AI Technical Summary
During the use of the existing coolant, the conductivity increases and fails due to the accumulation of anion and cations. The added organic corrosion inhibitor coolant has poor stability, short service life and high cost.
The anion adsorbent and cationic adsorbent of porous magnesium silicate-based anionic adsorbent are introduced into the ethylene glycol/water coolant. By adsorbing the anions and cations generated in the coolant, the total concentration is reduced and the conductivity is maintained at an extremely low level.
It significantly reduces the total concentration of anions and cations in the coolant, maintains low conductivity, extends the service life of the coolant, and is simple in preparation, low in cost, and is easy to produce in industrial use.
Smart Images

Figure CN115785916B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic functional material preparation, and in particular relates to a preparation method of a low-conductivity coolant and the low-conductivity coolant. Background Art
[0002] The engine cooling system is composed of multiple parts, including the water-cooling jacket, cylinder block, circulating water pump, inlet and outlet pipes, etc. The metal materials used in each part are also different, mainly including brass, aluminum alloy and carbon steel. The cooling system cannot perform its cooling function without coolant. Ethylene glycol coolant is often used as the heat transfer medium of the equipment cooling system due to its low freezing point, low corrosiveness, high specific heat capacity and excellent fluidity. Usually, ethylene glycol will adsorb on the metal surface to slow down the corrosion of the metal. In addition, some corrosion inhibitors in the coolant can isolate the corrosive medium from the metal matrix by passivating the metal surface or forming a deposited film on the metal surface, thereby reducing the corrosion of the metal material. Nevertheless, with the increase of service time, the corrosion of various components of the cooling system continues to increase, and a large number of anions and cations, such as Ca, will inevitably accumulate in the coolant. 2+ 、Al 3+ , Cl - 、SO4 2- Ions, etc., increase the conductivity and cause the coolant to fail.
[0003] In order to reduce the corrosion performance of the coolant, a heterocyclic nitrogen-containing compound corrosion inhibitor is usually added to the coolant. Document CN108102616A discloses a method for preparing a low-conductivity coolant with 8-hydroxyquinoline, uracil, 4-acetaminophen, benzotriazole octadecylamine, N-bromosuccinimide and inosine as main additives, and the conductivity can reach 0.08μS / cm; Document CN102174313B discloses a method for preparing a low-conductivity coolant with natural alkaloids, heterocyclic alkanes, and azole compounds as main additives, and the conductivity can reach 5μS / cm. The added organic nitrogen-containing compound can form a chelate on the metal surface to prevent further corrosion of the metal to reduce the conductivity of the coolant. Document CN109065912A reports a coolant with a new non-ionic corrosion inhibitor added, which can reduce the conductivity of the coolant, and has a good corrosion inhibition ability for iron and aluminum-based metals, and has a good cooling effect. However, these organic corrosion inhibitors have defects such as complex preparation conditions, high prices, and poor stability, which lead to problems such as poor stability, short service life, and high cost of coolants added with organic corrosion inhibitors, limiting their application in coolants. Therefore, it is urgent to develop new high-stability, low-cost coolant preparation technologies.
[0004] The present invention introduces anion adsorbent and cation adsorbent into ethylene glycol / water type coolant, and can in-situ adsorb anions and cations generated in the coolant, thereby significantly reducing the total concentration of anions and cations in the coolant, and keeping its conductivity at an extremely low level. The anion adsorbent and cation adsorbent provided by the present invention are porous magnesium silicate-based inorganic functional materials, which have a simple preparation method, high stability, and strong anti-aging ability, and can significantly improve the service life of the coolant. Summary of the invention
[0005] The invention uses sodium silicate and magnesium salt as raw materials, adopts a solvent thermal method to prepare a porous magnesium silicate adsorption material, then adopts a long-chain quaternary ammonium salt to perform surface modification on the magnesium silicate so that the surface of the magnesium silicate is positively charged, adds the porous magnesium silicate and the quaternary ammonium salt-modified magnesium silicate into ethylene glycol at a mass ratio of 1:1-1.5, grinds them uniformly to obtain a high-solid-content concentrated slurry with the magnesium silicate content of 20-40%, then adds the concentrated slurry into ethylene glycol and grinds them uniformly again to obtain an ethylene glycol coolant with the magnesium silicate solid content of 1-5%. The coolant has the advantages of low electrical conductivity, long service life, simple preparation method, low cost, easy industrial production and the like, and overcomes the problems of poor stability, short service life and high cost of a coolant with an organic corrosion inhibitor added therein.
[0006] The preparation method of the low-conductivity coolant of the present invention comprises the following specific steps: A. preparing a sodium silicate solution with a concentration of 0.5 to 2 mol / L using deionized water, and preparing a magnesium salt solution with a concentration of 0.5 to 2 mol / L using a mixed solution of ethanol and water with a volume ratio of 1:1 to 5; and mixing the mixture in a stirring state according to SiO3 2-The sodium silicate solution is added dropwise to the magnesium salt solution in a ratio of 1:1 / Mg molar ratio, and the addition is completed within 15-60 minutes to obtain a mixed slurry; the mixed slurry is heated to 140-190°C and reacted at a constant temperature for 3-12 hours at a rotation speed of 100-300 r / min; after the reaction, a first precipitate is obtained, the first precipitate is centrifuged and washed to neutrality, a part of which is stored as a wet filter cake for standby use, and the other part is dried at 50-140°C for 6-12 hours to obtain porous magnesium silicate; B. the wet filter cake washed clean in step A is added to ultrapure water, and ground with a colloid mill for 5-20 minutes to obtain a first slurry with a solid content of 2-10%, and the mass ratio of long-chain quaternary ammonium salt to magnesium silicate in the wet filter cake is 0.1-1 The method comprises the following steps: adding a long-chain quaternary ammonium salt to the first slurry at a ratio of 1:1, and then stirring and reacting at 90-140° C. for 3-12 hours; obtaining a second precipitate after the reaction is completed, centrifuging the second precipitate, washing it 5-8 times, and drying it at 60-100° C. for 6-12 hours to obtain a quaternary ammonium salt-modified magnesium silicate; C. adding the porous magnesium silicate obtained in step A and the quaternary ammonium salt-modified magnesium silicate obtained in step B to ethylene glycol at a mass ratio of 1:1-1.5, grinding them with a colloid mill for 5-20 minutes to obtain a second slurry with a magnesium silicate solid content of 20-40%, adding the obtained second slurry to a mixed solvent of ethylene glycol and water for dilution, and grinding them with a colloid mill again for 5-20 minutes to obtain an ethylene glycol / water type coolant.
[0007] Furthermore, the magnesium salt is any one of magnesium nitrate, magnesium chloride or magnesium sulfate.
[0008] Furthermore, the specific surface area of the porous magnesium silicate is 260 to 400 m 2 / g, and the average pore size is 5 to 10 nm.
[0009] Furthermore, the long-chain quaternary ammonium salt is any one of lauryl to hexadecyl trimethyl ammonium bromide or ammonium chloride.
[0010] Furthermore, the solid content of magnesium silicate in the ethylene glycol / water type coolant is 1-5%, and the conductivity of the ethylene glycol / water type coolant is 0.1-1 μS / cm.
[0011] The present invention also provides a low-conductivity coolant, which is prepared by the above-mentioned method for preparing the low-conductivity coolant.
[0012] Compared with the prior art, the present invention has the following beneficial effects:
[0013] The present invention captures anions and cations in the freezing liquid by adding anion and cation adsorbents, thereby reducing the free anions and cations in the freezing liquid. Since the adsorbent used is a porous magnesium silicate material, it has the characteristics of large adsorption capacity, high stability, convenient synthesis, etc. Therefore, the prepared coolant exhibits the advantages of low conductivity, long service life, simple preparation method, low cost, easy industrial production, etc., overcoming the problems of poor stability, short service life and high cost of the coolant added with organic corrosion inhibitor. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is the BET spectrum of the porous magnesium silicate prepared in Example 1.
[0015] Figure 2 The XRD spectra of the porous magnesium silicate and modified magnesium silicate prepared in Example 1 are shown.
[0016] Figure 3 The hexadecyltrimethylammonium bromide-modified porous magnesium silicate and the unmodified magnesium silicate prepared in Example 1 react with SO4 2- Ion adsorption kinetics curve. DETAILED DESCRIPTION
[0017] In order to enable those skilled in the art to better understand the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments.
[0018] Embodiment 1:
[0019] The steps for preparing the low conductivity coolant in this embodiment are as follows:
[0020] A: Weigh 28.4g Na2SiO3·9H2O and add it to 100mL deionized water, stir and dissolve to obtain Na2SiO3 solution; weigh 20.3g Mg(Cl)2·6H2O and add it to 300mL ethanol / water mixed solution with a volume ratio of 1:3, stir and dissolve to obtain magnesium chloride solution; under stirring conditions, add the sodium silicate solution dropwise to the magnesium chloride solution within 20 minutes to obtain mixing, after the dropwise addition is completed, transfer the mixed slurry to a hydrothermal reactor with stirring, heat it to 170°C, and then react at a constant temperature for 6 hours at a stirring speed of 100r / min. After the reactor is cooled to room temperature, a first precipitate is obtained, the first precipitate is centrifuged and washed to neutrality, a part of the wet filter cake is stored for use, and the other part of the wet filter cake is placed in a 70°C oven and dried for 8 hours to obtain porous magnesium silicate.
[0021] B: The clean wet filter cake in step A was added into 100 mL of ultrapure water, and ground with a colloid mill for 5 min to obtain a first slurry, 3 g of hexadecyltrimethylammonium bromide was weighed and added into the first slurry, and then stirred at 100° C. for 6 h; after the reaction, a second precipitate was obtained, which was centrifuged, washed 6 times, and dried at 90° C. for 8 h to obtain quaternary ammonium salt-modified magnesium silicate.
[0022] C: Weigh 2 grams of the porous magnesium silicate obtained in step A and 2 grams of the quaternary ammonium salt-modified magnesium silicate obtained in step B respectively, add them to 10 grams of ethylene glycol, grind them with a colloid mill for 10 minutes to obtain a second slurry, then add the second slurry to a mixed solvent consisting of 50 grams of ethylene glycol and 50 grams of water for dilution, and grind them with a colloid mill again for 5 minutes to obtain an ethylene glycol / water type coolant with a magnesium silicate solid content of 3.5%, and a conductivity of 0.4 μS / cm, which is a low conductivity coolant provided by the present invention.
[0023] Figure 1 The BET spectrum of the porous magnesium silicate prepared in step A of Example 1 has a specific surface area of 271 m 2 / g, and the average pore size is about 6.33nm. Figure 2 The XRD spectra of the porous magnesium silicate prepared in step A and the porous magnesium silicate modified with hexadecyltrimethylammonium bromide prepared in step B show that the modification process did not destroy the crystalline structure of the porous magnesium silicate. 2- It has almost no adsorption capacity for ions. Figure 3 The effect of hexadecyltrimethylammonium bromide on the porous magnesium silicate and unmodified magnesium silicate on SO4 2- The adsorption kinetic curve of magnesium silicate before modification on SO4 2- The ion has almost no adsorption capacity, and its equilibrium adsorption capacity after modification is 10.18 mg / g.
[0024] Embodiment 2:
[0025] A: Weigh 28.4g Na2SiO3·9H2O and add it to 200mL deionized water, stir and dissolve to obtain Na2SiO3 solution; weigh 20.3g Mg(Cl)2·6H2O and add it to 200mL ethanol / water mixed solution with a volume ratio of 1:4, stir and dissolve to obtain magnesium chloride solution; under stirring conditions, add the sodium silicate solution dropwise to the magnesium chloride solution within 10 minutes to obtain a mixed slurry, after the dropwise addition is completed, transfer the mixed slurry to a hydrothermal reactor with stirring, heat it to 150°C, and then react at a constant temperature for 6 hours at a stirring speed of 200r / min. After the reactor is cooled to room temperature, a first precipitate is obtained, the first precipitate is centrifuged and washed to neutrality, a part of the wet filter cake is stored for use, and the other part of the wet filter cake is placed in a 90°C oven and dried for 6 hours to obtain porous magnesium silicate.
[0026] B: The clean wet filter cake obtained in step A is added into 150 mL of ultrapure water, and ground with a colloid mill for 10 min to obtain a first slurry, 2 g of dodecyltrimethylammonium bromide is weighed and added into the first slurry, and then stirred for reaction at 120° C. for 4 h; after the reaction is completed, a second precipitate is obtained, which is centrifuged, washed 5 times, and dried at 80° C. for 10 h to obtain quaternary ammonium salt-modified magnesium silicate.
[0027] C: Weigh 2 grams of the porous magnesium silicate obtained in step A and 2.5 grams of the quaternary ammonium salt-modified magnesium silicate obtained in step B respectively, add them to 10 grams of ethylene glycol, grind them with a colloid mill for 5 minutes to obtain a second slurry, then add the second slurry to a mixed solvent consisting of 50 grams of ethylene glycol and 100 grams of water for dilution, and grind them with a colloid mill again for 10 minutes to obtain an ethylene glycol / water type coolant with a magnesium silicate solid content of 2.7%, and a conductivity of 0.56 μS / cm, which is a low conductivity coolant provided by the present invention.
[0028] Embodiment 3:
[0029] A: Weigh 42.6g Na2SiO3·9H2O and add it to 300mL deionized water, stir and dissolve to obtain Na2SiO3 solution; weigh 30.45g Mg(Cl)2·6H2O and add it to 400mL ethanol / water mixed solution with a volume ratio of 1:3, stir and dissolve to obtain magnesium chloride solution; under stirring conditions, add the sodium silicate solution dropwise to the magnesium chloride solution within 30 minutes to obtain a mixed slurry, after the dropwise addition is completed, transfer the mixed slurry to a hydrothermal reactor with stirring, heat it to 180°C, and then react at a constant temperature for 5 hours at a stirring speed of 300r / min. After the reactor is cooled to room temperature, a first precipitate is obtained, the first precipitate is centrifuged and washed to neutrality, a part of the wet filter cake is stored for use, and the other part of the wet filter cake is placed in a 100°C oven and dried for 5 hours to obtain porous magnesium silicate.
[0030] B: The clean wet filter cake obtained in step A was added into 150 mL of ultrapure water, and ground with a colloid mill for 8 min to obtain a first slurry, 3 g of hexadecyltrimethylammonium chloride was weighed and added into the first slurry, and then stirred and reacted at 130° C. for 7 h; after the reaction, a second precipitate was obtained, which was centrifuged, washed 6 times, and dried at 90° C. for 8 h to obtain quaternary ammonium salt-modified magnesium silicate.
[0031] C: Weigh 3 grams of the porous magnesium silicate obtained in step A and 3 grams of the quaternary ammonium salt-modified magnesium silicate obtained in step B respectively, add them to 10 grams of ethylene glycol, grind them with a colloid mill for 10 minutes to obtain a second slurry, then add the second slurry to a mixed solvent consisting of 184 grams of ethylene glycol and 300 grams of water for dilution, and grind them with a colloid mill again for 5 minutes to obtain an ethylene glycol / water type coolant with a magnesium silicate solid content of 1.2%, and a conductivity of 0.8 μS / cm, which is a low conductivity coolant provided by the present invention.
[0032] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a low conductivity coolant, the specific steps are as follows: A. Prepare a sodium silicate solution with a concentration of 0.5-2 mol / L using deionized water, and a magnesium salt solution with a concentration of 0.5-2 mol / L using a mixed solution of ethanol and water with a volume ratio of 1:1-5; under stirring, 2- The sodium silicate solution is added dropwise to the magnesium salt solution at a molar ratio of Mg / Mg of 1, and the addition is completed within 15 to 60 minutes to obtain a mixed slurry; At a speed of 100 to 300 r / min, the mixed slurry is heated to 140 to 190° C. and reacted at a constant temperature for 3 to 12 hours; after the reaction, a first precipitate is obtained, the first precipitate is centrifuged and washed to neutrality, a portion of which is stored as a wet filter cake for later use, and the other portion is dried at 50 to 140° C. for 6 to 12 hours to obtain porous magnesium silicate; B. adding the wet filter cake washed in step A into ultrapure water, grinding with a colloid mill for 5 to 20 minutes to obtain a first slurry with a solid content of 2 to 10%, adding a long-chain quaternary ammonium salt to the first slurry in a ratio of 0.1 to 1:1 of the mass ratio of the long-chain quaternary ammonium salt to the magnesium silicate in the wet filter cake, and then stirring and reacting at 90 to 140° C. for 3 to 12 hours; after the reaction is completed, a second precipitate is obtained, the second precipitate is centrifuged, washed 5 to 8 times, and dried at 60 to 100° C. for 6 to 12 hours to obtain quaternary ammonium salt-modified magnesium silicate; C. The porous magnesium silicate obtained in step A and the quaternary ammonium salt-modified magnesium silicate obtained in step B are added to ethylene glycol in a mass ratio of 1:1 to 1.5, and ground with a colloid mill for 5 to 20 minutes to obtain a second slurry with a magnesium silicate solid content of 20 to 40%, and the obtained second slurry is added to a mixed solvent of ethylene glycol and water for dilution, and ground with a colloid mill again for 5 to 20 minutes to obtain an ethylene glycol / water type coolant.
2. The method for preparing a low-conductivity coolant according to claim 1, characterized in that: The magnesium salt is any one of magnesium nitrate, magnesium chloride or magnesium sulfate.
3. The method for preparing a low-conductivity coolant according to claim 1 or 2, characterized in that: The specific surface area of the porous magnesium silicate is 260 to 400 m 2 / g, and the average pore size is 5 to 10 nm.
4. The method for preparing a low-conductivity coolant according to claim 1 or 2, characterized in that: The long-chain quaternary ammonium salt is any one of dodecyl to hexadecyl trimethyl ammonium bromide or dodecyl to hexadecyl trimethyl ammonium chloride.
5. The method for preparing a low-conductivity coolant according to claim 1, characterized in that: The magnesium silicate solid content of the ethylene glycol / water type coolant is 1-5%, and the electrical conductivity of the ethylene glycol / water type coolant is 0.1-1 μS / cm.
6. A low conductivity coolant, characterized in that: The low-conductivity coolant is prepared by the method for preparing the low-conductivity coolant according to any one of claims 1 to 5.
Citation Information
Patent Citations
Low-conductivity super-long-acting organic base type anti-freezing cooling liquid
CN102174313B
Organic fuel cell anti-freeze cooling liquid with low conductivity and ultra-long acting and preparation method of anti-freeze cooling liquid
CN108102616A
A coolant added with a new non-ionic corrosion inhibitor and its application
CN109065912A
Environment-friendly engine coolant
CN105419747A
Method for preparing porous magnesium silicate by using ball milling method and prepared magnesium silicate
CN113120914A